Selective Monoarylation of Primary Amines Using the Pd‐PEPPSI‐IPentCl Precatalyst1. Issue 33 (10th June 2015) - Sharif, Sepideh; Rucker, Richard P.; Chandrasoma, Nalin; Mitchell, David; Rodriguez, Michael J.; Froese, Robert D. J.; Organ, Michael G.
Abstract A single set of reaction conditions for the palladium‐catalyzed amination of a wide variety of (hetero)aryl halides using primary alkyl amines has been developed. By combining the exceptionally high reactivity of the Pd‐PEPPSI‐IPentCl catalyst (PEPPSI=pyridine enhanced precatalyst preparation, stabilization, and initiation) with the soluble and nonaggressive sodium salt of BHT (BHT=2, 6‐di‐tert‐butyl‐hydroxytoluene), both six‐ and five‐membered (hetero)aryl halides undergo efficient and selective amination.